Richard Wagner.: 1813-1883 - Unknown:::Creator::::::::::::; Perry, Eugene A. (Eugene Ashton), 1864-1948 (publisher):::Contributor:::::::::::: (United States; Malden, Massachusetts; Eugene A. Perry)
Reprint of a photograph of Richard Wagner.